Effect of mental fatigue on decision-making skill and visual search behaviour in basketball players: an experimental and randomised study - Fortes, L. S.; Lima-Junior, D.; Barbosa, B. T.; Faro, H. K. C.; Ferreira, M. E. C.; Almeida, S. S. (International Journal of Sport and Exercise Psychology, 2025)
The objective was to analyze the effect of mental fatigue induced by a prolonged period of a sport-based videogame on decision-making skill and visual search behaviour in basketball players. Sixteen male basketball players participated in the study. The experiment was a randomised counterbalanced crossover design. They underwent the two experimental conditions [Control (CON) and videogame (VID)], interspersed by a one-week washout interval. We measured decision-making skill and visual search behaviour before (baseline) and after cognitive manipulations (VID and CON) in the two experimental sessions. Accuracy decreased, and the decision-making response time increased only in the VID condition (p < 0.05). The number of fixations only changed for the VID condition (p < 0.05), while the duration of fixations remained similar in both experimental conditions (p > 0.05). The mental fatigue induced by sport-based videogame impaired decision-making and altered visual search behaviour in basketball players.